From Feed to Fame: Analyzing the Influence of Instagram Marketing on Carasun’s Brand Image - Jihan Kinanti, Zalfa; Thoyib Amali, Muhammad (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
The rapid growth of internet users in Indonesia has encouraged businesses to expand their marketing activities through social media platforms. Among these, Instagram has emerged as one of the most popular tools for digital marketing communication. Its interactive features, such as comments and direct messages, enable companies to engage directly with consumers, making it an effective medium for brand promotion and image building. This study investigates the influence of Instagram marketing on the brand image of Carasun, a local sunscreen brand that recently gained viral attention due to its controversial marketing campaigns. Employing an explanatory quantitative approach, the research collected data from 396 respondents who are beauty enthusiasts and followers of Carasun’s official Instagram account. The data, measured using a Likert scale through an online questionnaire, were analyzed using simple linear regression. The findings reveal that Instagram marketing has a significant positive impact on Carasun’s brand image, with a contribution of 48.5% and a significance level of p < 0.05. Theoretically, this study enriches the understanding of how social media marketing activities influence brand perception. Practically, it offers valuable insights for marketers in designing content strategies that foster consumer engagement, strengthen purchase intentions, and sustain a positive brand image.